Anomalous single‐subject based morphological cortical networks in drug‐naive, first‐episode major depressive disorder. Issue 5 (8th February 2017) - Chen, Taolin; Kendrick, Keith M.; Wang, Jinhui; Wu, Min; Li, Kaiming; Huang, Xiaoqi; Luo, Yuejia; Lui, Su; Sweeney, John A.; Gong, Qiyong
Abstract: Major depressive disorder (MDD) has been associated with disruptions in the topological organization of brain morphological networks in group‐level data. Such disruptions have not yet been identified in single‐patients, which is needed to show relations with symptom severity and to evaluate their potential as biomarkers for illness. To address this issue, we conducted a cross‐sectional structural brain network study of 33 treatment‐naive, first‐episode MDD patients and 33 age‐, gender‐, and education‐matched healthy controls (HCs). Weighted graph‐theory based network models were used to characterize the topological organization of brain networks between the two groups. Compared with HCs, MDD patients exhibited lower normalized global efficiency and higher modularity in their whole‐brain morphological networks, suggesting impaired integration and increased segregation of morphological brain networks in the patients. Locally, MDD patients exhibited lower efficiency in anatomic organization for transferring information predominantly in default‐mode regions including the hippocampus, parahippocampal gyrus, precuneus and superior parietal lobule, and higher efficiency in the insula, calcarine and posterior cingulate cortex, and in the cerebellum. Morphological connectivity comparisons revealed two subnetworks that exhibited higher connectivity strength in MDD mainly involving neocortex‐striatum‐thalamus‐cerebellum and thalamo‐hippocampal circuitry. MDD‐related alterations correlated with symptom severity and differentiated individuals with MDD from HCs with a sensitivity of 87.9% and specificity of 81.8%. Our findings indicate that single subject grey matter morphological networks are often disrupted in clinically relevant ways in treatment‐naive, first episode MDD patients. Circuit‐specific changes in brain anatomic network organization suggest alterations in the efficiency of information transfer within particular brain networks in MDD. Hum Brain Mapp 38:2482–2494, 2017 . ©2017 Wiley Periodicals, Inc.